Perinatal and Prenatal Disorders - Dennery, Phyllis A.; Dennery, Phyllis A.; Buonocore, Giuseppe.; Buonocore, Giuseppe.; Saugstad, Ola Didrik.; Saugstad, Ola Didrik. (Oxidative Stress in Applied Basic Research and Clinical Practice,, 2014)
This authoritative volume describes the role of free radicals and antioxidants in prenatal and perinatal disorders currently explored in clinical and pre-clinical trials. In twenty-two inclusive chapters, the book covers the gamut of oxidative stress and its relation to a variety of factors, including fertility, metabolism, redox biomarkers, antioxidant defense and protection, gene polymorphisms, angiogenesis, cell signaling, mutations and oxidative damage involving lipids, proteins and nucleic acids, membrane trafficking, inflammation, mitochondrial dysfunction, alterations in immunological function, hypoxia, and post-natal stressors. This comprehensive source will keep clinicians and research scientists up-to-date on translational research into medical applications. Perinatal and Prenatal Disorders is a significant addition to the well-known Oxidative Stress in Applied Basic Research and Clinical Practice series.